RISK FACTORS, MATERNAL, AND PERINATAL OUTCOME OF FETAL MACROSOMIA - Pidugu, Sree Sailaja; BODDEDA, MOUNISHA NV; RANI, BALLA SUDHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Macrosomia is characterized by a birth weight exceeding 4000 g, regardless of gestational age, or >90th percentile for gestational age. This condition is linked to significant risks of maternal and neonatal morbidity and mortality. Globally, the prevalence of infants weighing ≥4000 g is estimated to be 9%. Various risk factors contribute to the development of fetal macrosomia, including a high pre-pregnancy body mass index (BMI), excessive weight gain during the antenatal period, high parity, male gender of the fetus, prolonged pregnancy, and maternal diabetes mellitus. Methods: A retrospective cross-sectional study was undertaken in the Department of Obstetrics and Gynecology at GIMSR Teaching Hospital, over a 5-year period from May 2018 to May 2023. The study encompassed all singleton pregnancies with a birth weight equal to or exceeding 4000 g, irrespective of the delivery method. Maternal and neonatal records for the study population were systematically collected, and data were documented. Results: Throughout the study duration, there were 167 cases where the birth weight equalled or exceeded 4,000 g. Most common maternal complication was prolonged labor and postpartum hemorrhage. Shoulder dystocia was seen in 2.9% of all deliveries and 10.8% of all vaginal deliveries. Most common neonatal complication was hypoglycemia. Conclusion: The prevalence of macrosomia in our study was 3.86%. Main risk factors identified in our study were male gender, pre pregnancy BMI >25, previous macrosomic births, and excessive weight gain during pregnancy.